Faktor - Faktor yang Berhubungan dengan Minat dan Motivasi Nursepreneurship Mahasiswa Keperawatan: Factors Related to Nursing Students' Interests and Motivation for Nursepreneurship - Musta'in, Mukhammad; Maksum; Susilo, Tri; Sugiarto, Heri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
Entrepreneurship is an activity to become productive that is not limited by space, time, place, age, and gender, including the field of nursing known as nursepreneurship. The spirit of nursepreneurship needs to be nurtured early on in nursing students considering the increasingly limited job vacancies in hospitals. This study aims to identify the factors related to the interest and motivation of nursing students in pursuing nursepreneurship. The research method is an analytical survey with a cross-sectional approach. The research subjects are sixth-semester students who have taken the nursepreneurship course, using total sampling technique with a total of 30 respondents. The research results showed that 83.3% of the respondents were female and 16.7% were male. The age of the respondents: 19 years 6.7%, 20 years 3.3%, 21 years 60%, 22 years 23.3%, 23 years 3.3%, and 24 years 3.3%. Parental entrepreneurship history: no 63.3% and yes 36.7%. The interest in nursepreneurship in the high category reached 83.3% and very high 16.7%, and the motivation for nursepreneurship in the high category reached 63.3% and very high 36.7%. The p-Value indicates the relationship between gender and interest in nursepreneurship is 0.183, the relationship between gender and motivation for nursepreneurship is 0.047, the relationship between parental entrepreneurship history and interest in nursepreneurship is 0.047, and the relationship between parental history and motivation for nursepreneurship is 0.238. The conclusion of the study is that the factors related to nursepreneurship motivation are gender, and the factor related to nursepreneurship interest is the entrepreneurial background of the parents. Further research is needed regarding other factors related to interest and motivation in nursepreneurship. ABSTRAK Wirausaha merupakan kegiatan untuk menjadi produktif yang tidak terbatas pada ruang, waktu, tempat, usia, dan jenis kelamin, tak terkecuali bidang keperawatan yang dikenal dengan nursepreneurship. Jiwa nursepreneurship perlu dipupuk sejak dini pada mahasiswa keperawatan mengingat semakin terbatasnya lowongan pekerjaan keperawatan di rumah sakit. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan minat dan motivasi mahasiswa keperawatan dalam mengikuti nursepreneurship. Metode penelitian adalah survey analitik dengan pendekatan crossectional. Objek penelitian adalah mahasiswa semester VI yang telah mengambil mata kuliah nursepreneurship dengan teknik total sampling sejumlah 30 responden. Hasil penelitian didapatkan responden berjenis kelamin perempuan sebanyak 83.3%, laki- laki 16.7%. Usia responden 19 tahun 6.7%, 20 tahun 3.3%, 21 tahun 60%, 22 tahun 23.3%, 23 tahu 3.3% dan 24 tahun 3.3%. Riwayat orangtua berwirausaha kategori tidak 63.3% dan ya 36.7%. Minat nursepreneurship kategori tinggi mencapai 83.3% dan sangat tinggi 16.7% dan motivasi nursepreneurship kategori tinggi 63.3% dan sangat tinggi 36.7%. Nilai p-Value didapatkan hubungan antara jenis kelamin dengan minat nursepreneurship sebesar 0.183, hubungan antara jenis kelamin dengan motivasi nursepreneurship sebesar 0.047, hubungan riwayat orang tua berwirausaha dengan minat nursepreneurship sebesar 0.047 dan hubungan riwayat orang tua dengan motivasi nursepreneurship 0.238. Simpulan penelitian yaitu faktor yang berhubungan dengan motivasi nursepreneurship yaitu jenis kelamin dan faktor yang berhubungan dengan minat nursepreneurship yaitu riwayat orang tua berwirausaha. Perlu penelitian lebih lanjut terkait faktor-faktor lain yang berhubungan dengan minat dan motivasi nursepreneurship.